Botanical, phytochemical, and bioactivity characterization of Coleus scutellarioides - KARTINI KARTINI; RIZKYA AJENG SHEVIRA SHEVIRA; FINNA SETIAWAN; ADITYA TRIAS PRADANA; AZMINAH AZMINAH; JOHAN SUKWEENADHI; A’LIYATUR ROSYIDAH; RETNO WIDYOWATI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Kartini K, Shevira RA, Setiawan F, Pradana AT, Azminah A, Sukweenadhi J, Rosyidah A, Widyowati R. 2025. Botanical, phytochemical, and bioactivity characterization of Coleus scutellarioides. Biodiversitas 26: 3623-3633. Coleus scutellarioides, commonly known as miana in Indonesia, is a versatile ornamental plant with a longstanding history of traditional medicinal use, particularly for treating inflammation and metabolic disorders. This study focuses on the purple variety due to its prevalence in traditional medicine and its distinctive features, including deep purple foliage with serrated margins. A comprehensive characterization was conducted, including botanical identification, physicochemical tests, and spectroscopic analysis (TLC, ATR-FTIR) to support its standardization as a medicinal crude drug. Biological activities were assessed for in vitro antioxidant (DPPH, NO) and enzyme inhibition (?-glucosidase, ?-amylase, xanthine oxidase) assays. Botanical analysis confirmed distinct morphological and microscopic traits, aiding in varietal identification. The physical evaluation yielded acceptable standardization values: loss on drying (8.86% w/w), total ash (9.35% w/w), and acid-insoluble ash (2.57% w/w). The thick extract exhibited a moisture content of 20.04% w/w, with total and acid-insoluble ash contents of 5.44% w/w and 3.72% w/w, respectively. Thin layer chromatography and spectral analysis confirmed the presence of flavonoids and phenolic acids, with total flavonoid contents of 0.59 mg QE/g (crude drug, i.e., dried plant material prior to extraction) and 1.64 mg QE/g (concentrated extract). Extractive values indicated that water-soluble constituents dominate. Biological assays demonstrated significant antioxidant activity (IC?? = 70.06 µg/mL), moderate ?-glucosidase (IC?? = 630 µg/mL), weak xanthine oxidase (IC?? = 900 µg/mL) and nitric oxide (IC?? = 2.52×10³ µg/mL) inhibition, but no ?-amylase inhibition activity. These findings support the traditional use of C. scutellarioides and provide scientific evidence for its potential as a natural remedy for oxidative stress and metabolic disorders.